2013
DOI: 10.1364/boe.4.000696
|View full text |Cite
|
Sign up to set email alerts
|

In vivo quantification of the scattering properties of tissue using multi-diameter single fiber reflectance spectroscopy

Abstract: Multi diameter single fiber reflectance (MDSFR) spectroscopy is a non-invasive optical technique based on using multiple fibers of different diameters to determine both the reduced scattering coefficient (μs′) and a parameter γ that is related to the angular distribution of scattering, where γ = (1-g2)/(1-g1) and g1 and g2 the first and second moment of the phase function, respectively. Here we present the first in vivo MDSFR measurements of μs′(λ) and γ(λ) and their wavelength dependence. MDSFR is performed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 28 publications
3
72
0
Order By: Relevance
“…In general, probes with longer emission wavelengths can be imaged with higher quality owing to reduced light scattering and tissue autofluorescence. In particular, light scattering decreases monotonically as emission wavelength increases (9,28,29). According to their fluorescence emission spectra, we chose optical filter sets of two 1,400-nm long pass + two 1,575-nm band pass, two 1,300-nm long pass + two 1,375-nm band pass, two 1,300-nm long pass, and two 1,100-nm long pass + two 1,125-nm band pass for DCNPs, QDs, SWNTs, and dye complex, respectively, to maximize each probe's signal-to-noise ratio (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…In general, probes with longer emission wavelengths can be imaged with higher quality owing to reduced light scattering and tissue autofluorescence. In particular, light scattering decreases monotonically as emission wavelength increases (9,28,29). According to their fluorescence emission spectra, we chose optical filter sets of two 1,400-nm long pass + two 1,575-nm band pass, two 1,300-nm long pass + two 1,375-nm band pass, two 1,300-nm long pass, and two 1,100-nm long pass + two 1,125-nm band pass for DCNPs, QDs, SWNTs, and dye complex, respectively, to maximize each probe's signal-to-noise ratio (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10] However, recent work showed that a range of γ values (for the same μ 0 s , μ a , and d det ) can result in the same reflectance.…”
Section: Introductionmentioning
confidence: 99%
“…Each layer in the phantom is characterized by its intrinsic optical properties like absorption coefficient μ a (λ), scattering coefficient μ s (λ), anisotropy factor g(λ) and refractive index n(λ) as a function of wavelength λ(nm). The typical values of these parameters in the visible wavelength range were based on reported literature [25, [39][40][41][42][43][44][45][46][47][48]. Volume fraction of melanosomes which corresponds to the optical absorption coefficient μ aepi (λ) of the epidermis is taken as 2% (for light pigmented skin) for the present study [42].…”
Section: Optical Properties Of the Phantommentioning
confidence: 99%
“…Scattering coefficients μ s (λ) and anisotropy g(λ) of epidermal and dermal layers of normal tissues and dysplastic conditions were approximated using the relations given in literature [40]. Scattering properties of polystyrene microspheres mentioned in Table 1 is found to match with the scattering properties of both the layers [39,41,47]. Different concentrations of FAD representing normal and abnormal conditions [25,45] were also chosen for the current study as presented in Table 1.…”
Section: Optical Properties Of the Phantommentioning
confidence: 99%